Порошковые магнитопроводы для магнитоэлектрических машин - Антонов, А.Е.; Филоменко, А.А. (Інститут електродинаміки НАН України, 2014)
Экспериментально определены частотные зависимости потерь на вихревые токи и гистерезис в магнитопроводах, изготовленных методом порошковой металлургии из различных исходных материалов. Изложена методика эксперимента, приведены кривые потерь. Експериментально визначено частотні залежності втрат на вихрові струми та втрат на гістерезис в магнітопроводах, виготовлених методом порошкової металургії з різних вихідних матеріалів. Викладено методику експерименту та подано криві загальних втрат вихідних матеріалів. Experimentally determined frequency dependence of the loss whirling currents and hysteresis in magnetic conductors for brushless magnetoelectric motors type manufactured by powder metallurgy from various starting materials. The method of experimental determination of magnetic losses is expounded. A research purpose consisted of search of the best chemical composition of ferromagnetic powder for stationary magnetic conductors, and also amount of polymeric minimum of electromagnetic losses connective on a criterion in magnetic conductors. Frequency dependences of losses in magnetic conductors are got. The minimum losses are provided in magnetic conductors, which are made from amorphous iron, PASC-60 powder and clean iron with the 1% and 5% the polymer amount. It is set that in the range of frequencies of magnetic reversal 200 Hertzs in them have character of growth of losses practically linear character.